JUAL BELI KULIT HEWAN QURBAN MENURUT HUKUM ISLAM - Yusriadi Yusriadi; Junawati Junawati (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2019)
This research is to reveal the practice of buying and selling Qurbananimal skin in Jeurat Manyang settlement and the purpose of buying and sellingQurban animal skin in kemukiman and how the Islamic law reviews the buyingand selling of Qurban animal skin. This research is a type of qualitative research,with data collection techniques, namely through interviews and documentation.The results showed that the practice of buying and selling Qurban animal skin inJeurat Manyang Settlement was indeed done, with a qabul permit process betweensellers and buyers. The Committee and also the Religious Figures as a guide to theextent to which the application of Islamic law is carried out in the community inaccordance with the Ulama's view. The data collection technique of this researchis interviews and documentation. The results showed that the sale of Qurbananimal skin was indeed done. This is based on the agreement of the ReligiousLeaders and the committee, because the sale of Qurban animal skin is more usefulthan distributed to the community, because the community itself does not want toprocess it. Sales made are in accordance with Islamic law because this is moreuseful